Studies into the reduction of domestic fuel burning emissions by means of facile catalytic abatement technology - Steyn, Marilize; Claassen, Nicolaas; Forbes, Patricia (Clean Air Journal, 2023)
The negative health and socio-economic impacts of emissions associated with domestic fuel burning are widely recognized. Although there has been much progress in the provision of electricity to households in South Africa, many still rely on solid fuel sources such as wood and coal. While various investigations have been done on reducing household emissions by reducing the use of polluting fuels and improvements in combustion efficiency, comparatively fewer studies have been conducted on the reduction of emissions through emission reduction using abatement technology. Catalytic oxidation could be utilized to oxidize particulate matter precursors such as volatile organic compounds and soot particles to reduce secondary particulate formation. Although catalytic methods have not been effectively utilized in practical domestic applications, studies have shown effective soot reduction during laboratory testing. This study investigated the synthesis and use of a manganese oxide based catalyst to reduce particulate matter from domestic fuel burning stoves. During field testing, the presence of the catalyst increased the mass of particulate matter collected, with Scanning Electron Microscopy (SEM) analysis showing spherical particles in the pores of the catalyst run filters. The baseline runs had very few of these particle clusters. Energy Dispersive X-Ray (EDX) analysis of the catalyst run filters did not detect manganese, revealing that increased particulate concentrations were not as a result of macroscopic particles of the catalyst being dislodged from the support. Dislodgement of very small metal particles from the catalyst could, however serve as nucleation nodes for particle growth which would have a non-metal coating leading to the non-detection of manganese. The increase in particulate matter could also be caused by the impingement of particulate matter precursors on the catalyst followed by particle growth and dislodgement into the flue gas. The testwork showed that an active catalyst can be synthesized onto a mesh catalyst support in a facile and cost effective manner, which can be utilized in domestic fuel burning devices. It is recommended that a range of optimized, potentially active catalysts be tested to improve the oxidation of particulate matter precursors to carbon dioxide.